STUDY OF NANOCRYSTAL ZINC SULPHIDE OBTAINED BY THE HYDROTHERMAL WAY - Abdullin, H. A.; Podrezova, L. V.; Bakranov, N. B.; Ermolaev, V. N.; Kudaibergenov, S. E.; Kumekov, S. E.; Seitov, A. S. (Recent Contributions to Physics, 2018)
The technique of sulfide zinc nanoparticles reception by the hydrothermal way from water solutions of precursors both in volume and on a substrate as thin ZnS films is developed.